2013
DOI: 10.1111/j.1440-1746.2012.07290.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel splice‐site mutation in ATP8B1 results in atypical Progressive Familial Intrahepatic Cholestasis Type 1

Abstract: This work expands the phenotypic spectrum of PFIC1, and highlights the overlap in clinical phenotype between Alagille syndrome and PFIC1. Knowledge of the causative mutation allows for carrier testing and prenatal diagnosis in this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…Interestingly, a homozygous splice site mutation preceding exon 16 of the ATP8B1 gene was previously reported in multiple affected individuals within another family with atypical PFIC1. The clinical presentation was similar to that of our patient, with an initial diagnosis of Alagille syndrome and clinical features including bile duct paucity, cardiac defects and renal tubular acidosis [Copeland et al, ]. The finding of mutations in ATP8B1 in these two families suggests that there may be a wider spectrum of disease resulting from defects in this gene, associated with previously unrecognized extrahepatic manifestations.…”
Section: To the Editorsupporting
confidence: 76%
“…Interestingly, a homozygous splice site mutation preceding exon 16 of the ATP8B1 gene was previously reported in multiple affected individuals within another family with atypical PFIC1. The clinical presentation was similar to that of our patient, with an initial diagnosis of Alagille syndrome and clinical features including bile duct paucity, cardiac defects and renal tubular acidosis [Copeland et al, ]. The finding of mutations in ATP8B1 in these two families suggests that there may be a wider spectrum of disease resulting from defects in this gene, associated with previously unrecognized extrahepatic manifestations.…”
Section: To the Editorsupporting
confidence: 76%
“…Furthermore, modifier genes have become increasingly recognized as an important source of phenotypic variation. Since the initiation of this study, another two intronic variants (c.1819+1G>A and c.1820‐1G>C) were reported that were not included . The latter was already characterized by using RNA from Epstein‐Barr virus–transformed lymphocytes from affected individuals and also caused missplicing resulting in a 4‐bp deletion from the 5' end of exon 16.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initiation of this study, another two intronic variants (c.181911G>A and c.1820-1G>C) were reported that were not included. 24,25 The latter was already characterized by using RNA from Epstein-Barr virus-transformed lymphocytes from affected individuals and also caused missplicing resulting in a 4-bp deletion from the 5' end of exon 16. As for most of the variants studied here, this frameshift will lead to a premature stop codon, likely resulting in mRNA and/or protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…If left untreated, PFIC1 may progress to liver fibrosis, cirrhosis and devastating end‐stage liver failure, eventually requiring liver transplantation in some cases. 2 , 3 , 4 , 5 , 6 The ATP8B1 gene is located on chromosome 18q21‐22 and encodes the familial intrahepatic cholestasis 1 (FIC1) protein, a P‐type ATPase in the P4 family that is involved in bile acid homeostasis and plays a critical role in bile secretion. 1 , 3 , 5 , 7 When the function of FIC1 is impaired due to ATP8B1 gene mutation, bile acids can accumulate, thus injure the hepatocytes and lead to cholestasis in PFIC1.…”
Section: Figurementioning
confidence: 99%